2000
DOI: 10.1111/j.1528-1157.2000.tb00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emotions in Children with Newly Diagnosed Epilepsy

Abstract: Summary:Purpose: To understand the emotional predicament in children with recently diagnosed idiopathic or cryptogenic epilepsy.Methods: We used the well-tried method of structured projection for the first time in children with epilepsy. Thirty-six children with epilepsy, aged 7-15 years (mean age, 9.5 years) and in 35 control children aged 7-15 years (mean age, 9.4 years), attributed shame and guilt in relation to three types of situation (non-illness related, illness related, and epilepsy related). Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Moreover, children with "epilepsy only" felt less socially accepted at school than their healthy classmates. This finding is in concordance with our earlier work (28). Using the method of structured projection, we showed that epilepsy-related situations are experienced as more shame provoking than are situations caused by other illnesses.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, children with "epilepsy only" felt less socially accepted at school than their healthy classmates. This finding is in concordance with our earlier work (28). Using the method of structured projection, we showed that epilepsy-related situations are experienced as more shame provoking than are situations caused by other illnesses.…”
Section: Discussionsupporting
confidence: 93%
“…Children who demonstrate both decreases in school self-concept and highseverity epilepsy have been found to be at most risk for educational problems over time (12). Lower selfesteem may result from the significant stigma that continues to be attached to epilepsy as both children with epilepsy and controls have been found to attribute more shame and guilt to incompetence due to epilepsy than to incompetence due to other illnesses (14).…”
Section: Introductionmentioning
confidence: 98%
“…Medically intractable epilepsy has repercussions that by far transgress the medical domain. Because of their unpredictability and their behavioral manifestations, seizures signify a loss of control that, if recurring in children, may foster a feeling of uncertainty (3,4). Feelings of not being in control of one's life are likely to be reinforced both by the necessity of antiepileptic drug (AED) use to prevent seizures and by the restrictions in activities of daily life that are imposed on children who are unaware of their seizures and, hence, of the cause of the restrictions.…”
mentioning
confidence: 99%